A Huge Anterior Urethral Diverticulum After Circumcision in a Child: An Unusual Complication of Disposable Plastic Circumcision Device - Özlem Balcı; İbrahim Karaman; Ayşe Karaman (Journal of Urological Surgery, 2019)

(untitled)
Urethral diverticula are very rare conditions in boys and may occur due to congenital or acquired reasons. Post-circumcision urethral diverticulum has not been previously reported in the literature. Here, we present a case of an acquired urethral diverticulum due to its unusual etiology.